Pengaruh Variasi Waktu Transesterifikasi dan Konsentrasi Katalis terhadap Karakteristik Sifat Fisik Biodiesel Berbahan Minyak Jelantah - Rosidah, Cicih; Nurul Fadhillah, Ghina; Rohmaful Aeni, Alfieta; Yuliasari, Fitri; Pangni Fahriani, Vera (Jurnal Teknik Terapan, 2025)
As a promising alternative fuel, biodiesel is expected  to grow in the future, aligning As part of global initiatives to lessen dependence on fossil fuels. This study focuses on using used cooking oil from frying chicken As a feedstock for biodiesel production through transesterification. The aim is to explore the effects of varying transesterification times and catalyst concentrations on the physical properties of the biodiesel produced, including density, viscosity, and yield. The method involves testing at different time intervals of 30, 40, and 50 minutes, with catalyst concentrations of 1%, 1.5%, and 2% to determine optimal conditions. Additionally, Fourier Transform Infrared (FTIR) tests were conducted to identify functional groups in the compounds.Results indicate that the highest biodiesel yield was achieved after 30 minutes of transesterification with a 1% catalyst concentration. The best viscosity was noted at 40 minutes with a 2% catalyst, while the optimal density was recorded at 30 minutes with a 2% catalyst.